Moral Readings of the Court: Discrimination Cases in the U.S. Supreme Court. (2nd November 2018) - Chilton, Bradley S.; Foyou, Viviane E.; King, Stephen M.
Abstract : What moral readings characterize contemporary U.S. Supreme Court opinions on discrimination by race; ethnicity; religion; gender; sexuality; and disabilities? John Rohr and the Constitutional School of Public Administration scholars have analyzed the Supreme Court's decisions for moral insights in public affairs. The authors sought to take a modest step with analysis based on a more nuanced, empirical moral reading of the Court's cases. First, the authors critiqued the case-study method of the Constitutional School, comparing these with moral readings of the Court's opinion, including moral justifications that are teleological and nonteleological. Second, the authors analyzed selected opinions by the contemporary Supreme Court on discrimination by race; ethnicity; religion; gender; sexuality; and disabilities. Third, the authors analyzed patterns of teleological (utilitarian or virtue) and nonteleological (deontological) moral justifications and concluded the Supreme Court ordinarily uses ethical arguments, often teleological (utilitarian), with nonteleological (deontological) justifications in cases of perceived injustice. Virtue moral justifications are rare: only with a nonvirtuous litigant. Thus, the authors meld a more nuanced, empirical moral reading with the traditional case-study method of the Constitutional School of Public Administration, without assuming appeal to some universal moral faculty—instead deferring to each person in accepting or rejecting these moral justifications.